Characterization of Nanosilver Biosynthesis by Citrus sinensis (L.) Osbeck and Peel-off Mask Formulation with Variation Polyethylene Glycol 400-Glycerin Concentration - Dian Eka Ermawati; Agung P. Surya; Adi Yugatama (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Sweet orange contains flavonoids and citric acid that have the potential as a capping agent in the nanosilver biosynthesis process. The antibacterial activity of silver can be increased in nanoparticles, then it can be applied to treat acne through a peel-off mask preparation. Glycerin and Polyethylene glycol 400 are humectants that combined to obtain good physicochemical properties of the preparation. This study aims to determine the character of nanosilver biosynthesis and the effect of humectant combination on the physicochemical properties of the preparation. The characterization of nanosilver was employed by UV-VIS Spectrophotometry, Particle Size Analysis, and Scanning Electron Microscope. The Glycerin- PEG 400 combination was F1 (0:100%); F2 (25:75%); F3 (50:50%); F4 (75:25%) and F5 (100:0%). The results of nanosilver biosynthesis have an absorption peak of nanoparticles at 421-423nm, rod shape, the particle size of 83.2±7.2nm. Statistical analysis showed that the combination of Glycerin- PEG 400 had a significant effect on organoleptic, viscosity, and dry time, but did not affect the pH of preparation. The combination of Glycerin-PEG 400 (75%:25%) is the best formula because it has stable viscosity, dry time, and pH value during storage for four weeks.Keywords: nanosilver, biosynthesis, Citrus sinensis, humectants, peel off mask